Application of Problem-Based Learning Model to Improve Student Activities and Learning Outcomes - Sarwandi; Norenta Sitohang; Mia Andriyani; Raudatul Izmi (Sean Institute, 2022)
The purpose of this study was to determine the activities and learning outcomes of students by applying the problem-based learning model in the Education Administration course at Budi Darma University. This research belongs to the type of classroom action research (Classroom Action Research) with the research subjects being students of the Information Technology Education study program with a total of 12 students, this research was conducted in two cycles and at the end of each cycle, there was a reflection on the actions that had been given. Data collection techniques in this study used observation sheets, questionnaires, and documentation. The results of this study indicate that the implementation of learning by applying the problem-based learning model can improve student activities and learning outcomes. This can be seen from the activeness of students in the first cycle with an average value of 62% and increased in the second cycle with an average value of 80%. Then from the results of student learning before applying the problem-based learning (pre-cycle) learning model with an average score of 12 students with 1 student who completed, after taking action in the first cycle with an average score of 39 with 5 students who completed, and after taking action in the second cycle with an average value of 73 with students who completed as many as 10 students. Judging from the activities and student learning outcomes, it is evident that the application of the problem-based learning model can improve student activities and learning outcomes.